Circulating levels of the terminal complement complex are associated with hypercoagulability in patients with stable coronary artery disease. Issue 196 (December 2020) - Kluge, Karsten E.; Langseth, Miriam S.; Bratseth, Vibeke; Pettersen, Alf Å.; Arnesen, Harald; Tønnessen, Theis; Seljeflot, Ingebjørg; Helseth, Ragnhild
Highlights: Complement and coagulation activation coincide in coronary artery disease (CAD). In CAD, complement activation coincides with endothelial activation and damage. In CAD, complement activation does not coincide with platelet activation. A novel link between immunity and hemostasis in CAD is demonstrated.